Adult onset global loss of the FTO gene alters body composition and metabolism in the mouse - McMurray, F; Church, C; Larder, R; Nicholson, G; Wells, S; Teboul, L; Tung, Y; Rimmington, D; Bosch, F; Jimenez, V; Yeo, G; O'Rahilly, S; et al. (Public Library of Science, 2013)
The strongest BMI-associated GWAS locus in humans is the FTO gene. Rodent studies demonstrate a role for FTO in energy homeostasis and body composition. The phenotypes observed in loss of expression studies are complex with perinatal lethality, stunted growth from weaning, and significant alterations in body composition. Thus understanding how and where Fto regulates food intake, energy expenditure, and body composition is a challenge. To address this we generated a series of mice with distinct temporal and spatial loss of Fto expression. Global germline loss of Fto resulted in high perinatal lethality and a reduction in body length, fat mass, and lean mass. When ratio corrected for lean mass, mice had a significant increase in energy expenditure, but more appropriate multiple linear regression normalisation showed no difference in energy expenditure. Global deletion of Fto after the in utero and perinatal period, at 6 weeks of age, removed the high lethality of germline loss. However, there was a reduction in weight by 9 weeks, primarily as loss of lean mass. Over the subsequent 10 weeks, weight converged, driven by an increase in fat mass. There was a switch to a lower RER with no overall change in food intake or energy expenditure. To test if the phenotype can be explained by loss of Fto in the mediobasal hypothalamus, we sterotactically injected adeno-associated viral vectors encoding Cre recombinase to cause regional deletion. We observed a small reduction in food intake and weight gain with no effect on energy expenditure or body composition. Thus, although hypothalamic Fto can impact feeding, the effect of loss of Fto on body composition is brought about by its actions at sites elsewhere. Our data suggest that Fto may have a critical role in the control of lean mass, independent of its effect on food intake.